Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $$T:V\longrightarrow W$$ be a linear map (of vector spaces), and let \begin{eqnarray} T^*:W^* &\longrightarrow& V^* \\ f\ &\longmapsto& f\circ T \end{eqnarray} be its transpose (or dual map).

How to show that if $T$ is injective then $T^*$ must be surjective, and that if $T$ is surjective then $T^*$ must be injective?

share|cite|improve this question
up vote 3 down vote accepted

For the case where $T$ is injective, suppose $a \in V^*$. We will define $b \in W^*$ such that $T^*(b) = b\circ T = a$. Let $W = T(V) \oplus W'$, i.e., $W'$ is the complementary subspace of $T(V)$ in $W$. For each $w \in W$, break it into $w = T(v) + w'$ where $v \in V$ and $w' \in W'$. This decomposition is unique (once $W'$ is chosen and is fixed). Since $T$ is injective, the map $w \mapsto v$ is well-defined, and so we can define $b(w) = b(T(v) + w') = a(v)$. It is easy to verify that now $(b \circ T)(v) = b(T(v)) = a(v)$ for all $v \in V$.

For the case where $T$ is surjective, suppose $b \in \ker(T^*)$, i.e., $(b \circ T)(v) = 0$ for all $v$. By surjectivity of $T$, this implies $b(W) = 0$, and so $b = 0$. Therefore, $\ker(T^*) = 0$.

share|cite|improve this answer

If $T$ is inejctive then it has a inverse $T^{-1}:T(V)\rightarrow V$. Take $v\in V^\star$ and define $f\in W^\star$ by $f(x)=v(T^{-1}(x))$. Then $T^\star(f)=f\circ T=v\circ T^{-1}\circ T=v$

On the other hand, suppose that $T$ is surjective. If $T^\star f=T^\star g$, then $f(T(x))=g(T(x))$ for all $x\in W$. Hence $(f-g)(T(x))=0$ for all $x\in W$. Because $T$ is surjective you can conclude that $f-g=0$, or $f=g$.

share|cite|improve this answer
In part 1: What is $T(W)$? I guess you mean $T(V)$, but what if $x\not\in T(V)$? – Spenser Jan 24 '13 at 1:52
In part 2: Why does the surjectivity of $T$ implies that $f-g=0$? – Spenser Jan 24 '13 at 1:56
@Spenser, I fixed part 1. In part 2, if you take any $y\in W$, you can find $x\in V$ such that $T(x)=y$. Then you have for all $y\in W$ that $(f-g)(y)=0$. This implies that $f-g=0$ – Tomás Jan 24 '13 at 10:49

Partial Solution:

$T$ is injective $\implies T^*$ is surjective: Choose $f\in V^*.$ We need to find out (using the injectivity of $T$) a linear transformation $f':W\to F$ such that $f'T=f.$ Let's try to reduce the proposed problem a bit more using the fact that two linear transformations agree everywhere if and only if they agree on a basis of the vector space considered as the domain. Thus our reduced task is to find out a linear transformation $f':W\to F$ such that $Tf'=f$ on a chosen basis of $V.$ The problem can a little more be reduced to define $f'$ using the fact that any mapping defined on a basis of a vector space extends to a unique linear transformation. Thus our aim is to define $f'$ on a basis of $W$ such that the effect of the composed map $f'T$ on the basis is identical with that of $f.$ How can it be done? Naturally by considering the effect of the pre-image when it exists (and here the injectivity comes into play) and nullify the effect otherwise. Can you construct $f'$ now?

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.